Epidermal growth factor receptor derived peptide vaccination to prevent lung adenocarcinoma formation: An in vivo study in a murine model of EGFR mutant lung cancer. Issue 11 (7th September 2015) - Ebben, Johnathan D.; Lubet, Ronald A.; Gad, Ekram; Disis, Mary L.; You, Ming
Abstract : The ability to prevent disease is the holy grail of medicine. For decades, efforts have been made to extend the successes seen with vaccination against infectious diseases to cancer. In some instances, preventive vaccination against viruses (prototypically HPV) has successfully prevented tumorigenesis and will make a major impact on public health in the decades to come. However, the majority of cancers that arise are a result of genetic mutation within the host, or non‐viral environmental exposures. We present compelling evidence that vaccination against an overexpressed self‐tumor oncoprotein has the potential to prevent tumor development. Vaccination against the Epidermal Growth Factor Receptor (EGFR) using a multipeptide vaccine in a preventive setting decreased EGFR‐driven lung carcinogenesis by 76.4% in a mouse model of EGFR‐driven lung cancer. We also demonstrate that anti‐EGFR vaccination primes the development of a robust immune response in vivo. This study provides proof of concept for the first time that targeting tumor drivers in a preventive setting in lung cancer using peptide vaccination can inhibit tumorigenesis and may provide useful clinical insights into the development of strategies to vaccinate against EGFR in populations where EGFR‐mutant disease is highly prevalent. © 2015 Wiley Periodicals, Inc.